Nutritional composition of bulla from cultivated enset [Ensete ventricosum (Welw.) Cheesman] landraces in central Ethiopia - Tesfaye Dilebo (Discover Food)
Abstract Enset is a versatile root crop predominantly utilized as a staple food for more than 25 million people living in Ethiopia. However, despite the presence of various landraces, their nutritional and ant-nutritional composition is not well understood. The purpose of this study was to ascertain the proximate composition, minerals, anti-nutritional factors, mineral bioavailability, pH, and titratability of the bulla contents from the eight commonly cultivated enset landraces. Each bulla sample was ground into a fine powder before being subjected to standard food analysis procedures. The nutritional profile of analyzed enset landraces varies significantly. The proximate content varies in moisture content (48.45–50.55%), crude protein (0.63–1.94%), crude fat (0.11–0.63%), crude fiber (0.46–1.03%), and total ash (1.10–2.21%), while the total carbohydrates came to 94.79–97.62%, and gross energy was 387.90–395.59 kcal/100 g. The mean contents of minerals (mg/100 g) on a dry weight basis ranged from (59.25–76.46) for calcium, potassium (83.54–129.61), magnesium (7.78–17.15), phosphorus (17.98–30.28), sodium (3.68–5.26), iron (3.62–5.52), and zinc (0.31–0.67). The mean anti-nutritional values (mg/100 g) for oxalate, tannin, and phytate ranged from 5.41 to 8.10, 1.65 to 2.12, and 11.75 to 23.68, respectively. Accordingly, the analyzed bulla samples showed a considerable nutritional value with minimal anti-nutritional components and molar ratios below critical values. This comprehensive approach enables the selection of nutritious bulla with desirable properties for local and regional use and promotes enset cultivation for food security.